Sixty-five papyrological texts : presented to Klaas A. Worp on the occasion of his 65th birthday - Bakker, M. J.; Hoogendijk, F. A. J.; Muhs, Brian Paul.; Worp, K. A. (Papyrologica Lugduno-Batava, 2008)
This volume contains editions of sixty-five Greek, Demotic, Coptic and Arabic texts from Egypt, contributed as a token of friendship and respect by forty-six of Klaas Worp's colleagues and co-authors upon his retirement from the Papyrological Institute of the University of Leiden in August 2008. The contents are as diverse as Klaas Worp's own wide range of interests, and provide a vivid impression of life and culture in Graeco-Roman Egypt. The texts are written on papyrus, potsherds, parchment, paper and wood. They include both literary and documentary papyri and ostraca, and date from the third century BC to the eleventh century AD. They are published fully, most for the first time, with transcriptions and translations, and are accompanied by photographs.